Plant community composition steers grassland vegetation via soil legacy effects. (7th April 2020) - Heinen, Robin; Hannula, S. Emilia; De Long, Jonathan R.; Huberty, Martine; Jongen, Renske; Kielak, Anna; Steinauer, Katja; Zhu, Feng; Bezemer, T. Martijn
Abstract: Soil legacy effects are commonly highlighted as drivers of plant community dynamics and species co‐existence. However, experimental evidence for soil legacy effects of conditioning plant communities on responding plant communities under natural conditions is lacking. We conditioned 192 grassland plots using six different plant communities with different ratios of grasses and forbs and for different durations. Soil microbial legacies were evident for soil fungi, but not for soil bacteria, while soil abiotic parameters did not significantly change in response to conditioning. The soil legacies affected the composition of the succeeding vegetation. Plant communities with different ratios of grasses and forbs left soil legacies that negatively affected succeeding plants of the same functional type. We conclude that fungal‐mediated soil legacy effects play a significant role in vegetation assembly of natural plant communities. Abstract : Under natural conditions, plant communities with different composition drive microbe‐mediated soil legacy effects on subsequent vegetation. Specifically, the abundance of forbs and grasses in vegetation can result in soil communities that negatively affect plants belonging to the same respective group. This study shows that plant–soil feedbacks occur in the field and are – in part – driven by pathogenic soil fungi.